Abdominal Compartment Syndrome Caused by Massive Pyonephrosis in an Infant with Primary Obstructive Megaureter - Silvia K. Kavaguti; Barbara R. Mackevicius; Murilo F. de Andrade; Silvio Tucci Jr; Ana P. C. P. Carlotti (Case Reports in Medicine)
The authors report a case of abdominal compartment syndrome caused by massive pyonephrosis in an infant with primary obstructive megaureter successfully treated with emergency surgical decompression.